2020
DOI: 10.1002/jctb.6522
|View full text |Cite
|
Sign up to set email alerts
|

Using taurine to increase mesopores in Ce‐based metal–organic framework for enhancing the production of 5‐hydroxymethylfurfural and 5‐ethoxymethylfurfural from fructose

Abstract: BACKGROUND: 5-hydroxymethylfurfural (HMF) and 5-ethoxymethylfurfural (EMF) are biomass-based value-added chemicals. Various catalytic systems have been studied for converting fructose into HMF and EMF. A more efficient and stable solid acid catalyst is highly desirable for the conversion process. RESULTS: In this study, a novel taurine-involved Ce metal organic framework material (T-CeMOF) was synthesized by coordinating Ce to 1,3,5-benzenetricarboxylic acid (BTC) in the presence of taurine. T-CeMOF was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…18 Sulfonic acid group functionalized solid acid catalysts are widely applied in biomass conversion including the production of EMF. 19 For instance, Wang et al 20 reported that HMF and EMF could be obtained in 67.2% and 11.2% yield from fructose which was catalyzed by the taurine-containing CeMOF material (T-CeMOF). Dai et al 21 investigated EMF production from fructose with a yield of 68.8% at 140 °C for 18 h via a sulfonated catalyst with a double-hydrogen-bond (D-SPC).…”
Section: Introductionmentioning
confidence: 99%
“…18 Sulfonic acid group functionalized solid acid catalysts are widely applied in biomass conversion including the production of EMF. 19 For instance, Wang et al 20 reported that HMF and EMF could be obtained in 67.2% and 11.2% yield from fructose which was catalyzed by the taurine-containing CeMOF material (T-CeMOF). Dai et al 21 investigated EMF production from fructose with a yield of 68.8% at 140 °C for 18 h via a sulfonated catalyst with a double-hydrogen-bond (D-SPC).…”
Section: Introductionmentioning
confidence: 99%
“…A normal yield of 71% for HMF conversion into EMF was detected over C-SO 3 H at 100 °C for 6 h with ethanol as a solvent. A novel Ce-MOF doped with taurine (T-CeMOF) was fabricated by bonding Ce to 1,3,5-benzenetricarboxylic acid (BTC) also accompanied by the taurine in this system, which transformed fructose into 69.6% EMF at 130 °C after 16 h in the ethanol/DMSO medium [76]. Catalyst characterization indicated that the surface of T-CeMOF existed with massive swinging of -COOH, and the -SO 3 H of taurine was successfully introduced into T-CeMOF.…”
Section: So 3 H-based Catalystsmentioning
confidence: 99%
“…13,14 EMF can be prepared from HMF by etherication reaction in high yields (>80%) with catalysts including mineral acids (e.g., sulfuric acid), heteropolyacids (e.g., phosphotungstic acid (H 3 PW 12 O 40 ) 15 ) or other solid acids (e.g., MOF-based heteropolyacid materials), 16 tungstophosphoric acid supported on mesoporous niobium oxophosphate 17 or MCM-41, 18 layered niobium-molybdate, 19 and Ag 1 H 2 PW (partially silver exchanged phosphotungstic acid). 20 When using fructose as feedstock, satisfactory EMF yields can also be achieved in the presence of a variety of homogeneous catalysts (e.g., sulfuric acid, 21 ZrOCl 2 $8H 2 O, 22 hydrogen sulfate ionic liquids, 23 deep eutectic solvent 24 ) or heterogeneous catalysts (e.g., sulfonic acidfunctionalized solid acids, [25][26][27][28][29] acidic nanospheres, 30 carbonaceous solid acids 12,31 ). Although the above-mentioned routes proceed easily and with high EMF yields, their large-scale applications are limited due to the high prices of fructose and HMF.…”
Section: Introductionmentioning
confidence: 99%